Preparation method and application of 3D printing ink based on soft magnetic nanoparticles
By combining soft magnetic nanoparticles with PDMS substrates, a high permeability 3D printing ink was prepared, which solved the problem of single function of existing 3D printing materials in magnetic shielding applications, and realized the magnetic shielding effect of 3D printing devices. Portable and miniaturized magnetic shielding devices in extremely weak magnetic field measurement devices.
Patent Information
- Application Number
- CN202411688263.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
AI Technical Summary
In the magnetic shielding application, existing 3D printing materials have problems such as single function and no magnetic shielding effect, especially in extremely weak magnetic field measurement devices, which are difficult to effectively shield the magnetic field.
Using 3D printing ink based on soft magnetic nanoparticles, 3D printing materials with high magnetic permeability are prepared by combining Fe3O4 nanoparticles, FeNi nanoparticles or CoFe nanoparticles with polydimethylsiloxane (PDMS) matrix. Used to print magnetic shielding helmets, cardiogram test panels and chip-level extreme weak magnetometer shielding devices.
The magnetic shielding effect of 3D printing devices is realized, meeting the needs of portability and miniaturization, and is suitable for brain magnetic testing devices and chip-level extreme weak magnetometers in medical devices, improving magnetic shielding performance.
Smart Images

Figure CN119432077A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnetic shielding materials, and in particular relates to a preparation method and application of 3D printing ink based on soft magnetic nanoparticles. Background Art
[0002] 3D printing, also known as additive manufacturing, is a material rapid prototyping technology. For polymer materials, the most direct contribution of 3D printing is that it can break free from the constraints of molds during the material molding process and form complex geometric shapes or structures. 3D printing is particularly suitable for the preparation of parts with personalized characteristics, and has demonstrated its value in the manufacture of small batches and personalized materials. These parts are widely needed in the fields of aerospace, biomedicine, etc. The emergence and development of 3D printing technology is based on the existing processing and molding technology of materials to meet the challenges of new material molding. 3D printing technology still has certain limitations. 3D printing materials have the disadvantages of few types and single functions, while nanocomposites have excellent properties such as sound, light, electricity, magnetism, heat, and force. Combining the two and designing 3D printed polymer-based nanocomposites can solve the problems of 3D printing materials.
[0003] The magnetic field strength of the earth's magnetic field is 50000nT. When using the extremely weak magnetic magnetometer without spin exchange (SERF) in quantum precision measurement to measure the magnetic field generated by the heart and brain, the magnetic field generated is very weak. If the external electromagnetic field is not shielded, the magnetic field generated by the heart and brain will be submerged in the external magnetic field. It is necessary to shield the external electromagnetic field and only measure the magnetic field signal generated by the heart and brain. Usually, magnetic shielding materials are required to shield the external magnetic field, and magnetic shielding rooms and magnetic shielding barrels will be built. These devices are bulky and difficult to move. In addition, during the test of the SERF magnetometer, some equipment will generate magnetic fields, which will affect the measurement of the magnetic field of the heart and brain. Therefore, it is necessary to consider using 3D printing technology to prepare magnetic shielding helmets or heart magnetic shielding equipment with magnetic shielding functions, which can be used to shield the magnetic field and can also achieve the characteristics of being portable, and can be used in portable new brain magnetic measurement devices. 3D printing technology can print personalized brain helmets and heart magnetic test panels, which can better match the test population and ensure the accuracy and specificity of the test. However, the materials used in 3D printing are generally polymer resin materials, so the prepared helmets or heart magnetic test panels do not have the effect of magnetic shielding. Adding soft magnetic nanoparticles (Fe 3 O 4 Nanoparticles, FeNi nanoparticles and CoFe nanoparticles, etc.) are used to prepare 3D printing ink with high magnetic conductivity, which is used for the use of helmets and heart magnetometry test panels in extremely weak magnetic magnetometers to measure heart and brain magnetism, and is also used for the use of devices for shielding magnetic fields in chip-level extremely weak magnetic magnetometers.
[0004] For low-frequency alternating current and static magnetic field, hysteresis and eddy current losses are small, so the principle of static magnetic field can be used for shielding. Shielding the geomagnetic field mainly shields the static magnetic field. The principle of static magnetic shielding is to use the magnetic circuit shunt principle, and use the high magnetic permeability and low magnetic resistance of soft magnetic materials to bypass the magnetic field. Ferromagnetic materials with relatively high magnetic permeability form a low magnetic resistance path, so that most of the magnetic lines of force of the static magnetic field pass through the magnetic shielding structure, and the magnetic flux entering the magnetic shielding area is small, thereby achieving the purpose of magnetic shielding. Generally, the magnetic shielding coefficient S is used for judgment and calculation.
[0005]
[0006] H 0 is the magnetic field strength in the space without shielding, H 1 The magnetic field strength of the area when shielding exists. The larger the S value, the better the shielding effect. For the shielding structure of a single-layer sphere under a static magnetic field, it can be calculated that:
[0007]
[0008] When the relative magnetic permeability of the shielding material is large enough and the thickness d of the shielding layer is very small, equation (1-2) can be simplified to:
[0009]
[0010] It can be seen that μ r The larger the d is, the larger the outer diameter R of the shielding structure is. 1 The smaller it is, the greater the shielding coefficient. In other words, the higher the magnetic permeability of the material, the thicker the shielding shell, and the smaller the shielding body, the better the shielding effect.
[0011] How to make the 3D printed helmet and cardiomagnetic device have magnetic shielding effect? Using polydimethylsioxlane (PDMS) as the base material, soft magnetic nanoparticles with high magnetic permeability (Fe 3 O 4 Nanoparticles, FeNi nanoparticles and CoFe nanoparticles) are used as fillers for 3D printing materials and added to PDMS. The ink direct writing 3D printing process is used to prepare 3D printed special-shaped brain helmets with high magnetic permeability, magnetic heart test panels and chip-level extremely weak magnetic magnetometer shielding devices, which are used as portable and miniaturized magnetic shielding devices. By using nanoparticles as fillers and applying them to 3D printing technology, the printed devices have magnetic shielding properties, which expands the application direction of 3D printing technology in portable magnetic shielding materials and devices, and has important academic research value.
[0012] The applicant has searched: the literature on 3D printing in the field of 3D printing technology using resin as a matrix and soft magnetic nanoparticles as fillers is shown in Table 1.
[0013] Table 1
[0014]
[0015]
[0016] In summary, with the development and popularization of 3D printing technology, some studies have mixed nanoparticles with different matrices for 3D printing to enhance the mechanical, thermal, optical and electromagnetic properties of printed devices. There are technical requirements for the shape and size of low-frequency magnetic shielding devices in extremely weak magnetic field measurement devices. In response to the above technical requirements, one technical route is to add soft magnetic nanoparticles to the 3D printed matrix to enhance the magnetic shielding performance of 3D printed materials.
[0017] However, in 3D printing technology, practical research on the soft magnetic properties of reinforced materials as magnetic shielding materials is still relatively lacking. Summary of the invention
[0018] The purpose of the present invention is to provide a preparation method and application of 3D printing ink based on soft magnetic nanoparticles in view of the above-mentioned deficiencies in the prior art.
[0019] The technical solution of the present invention is:
[0020] The preparation method of 3D printing ink based on soft magnetic nanoparticles comprises the following steps:
[0021] S100, preparing soft magnetic nanoparticles; the soft magnetic nanoparticles are Fe 3 O 4 Any one or more of nanoparticles, FeNi nanoparticles, and CoFe nanoparticles; the particle size of the soft magnetic nanoparticles is 5 to 30 nm;
[0022] S200, adding soft magnetic nanoparticles into PDSM, mixing evenly and removing bubbles to prepare soft magnetic material ink for direct writing 3D printing; the mass of the soft magnetic nanoparticles accounts for 20% to 40% of the sum of the mass of the soft magnetic nanoparticles and the PDSM.
[0023] Further, step S200 includes the following sub-steps:
[0024] S201, taking 1.0 g of PDSM and placing it in a 10 mL sample bottle, taking a certain amount of soft magnetic nanoparticles to be configured in a ratio of 20% to 40% by mass, and stirring evenly using a mixer to obtain a soft magnetic material ink for direct writing 3D printing;
[0025] S202, transferring the material into a 5.0 mL barrel, degassing it through a centrifuge, and then vacuuming it in a vacuum drying oven at room temperature to remove bubbles and organic matter, and repeating this operation 3 to 5 times until no bubbles are generated during vacuuming.
[0026] Furthermore, Fe 3 O 4 Preparation method of nanoparticles: Preparation of Fe by hydrothermal synthesis 3 O 4 Nanoparticles; weigh 2 mmol of Fe(acac) 3 Add seeds to a beaker, add 38 mL of alcohol and 2.4 mL of oleic acid, stir for 10 min to mix the solution evenly, add the mixed liquid to a 50 mL reactor, and react at 180 ° C in a forced air drying oven for 12 h; wash with alcohol and n-hexane alternately 3 times, and place the obtained product in a vacuum drying oven to dry (50 ° C, 4 h).
[0027] Further, the preparation method of FeNi nanoparticles is as follows: 1.5 mmol of Fe(NO 3 ) 3 9H 2 O and 1.0 mmol Ni(NO 3 ) 2 6H 2 O was added to 15 mL of deionized water, and then 15 mL of N-methylpyrrolidone was added thereto, and stirred for 10 minutes using a magnetic stirrer, and ultrasonicated until the material was evenly dispersed in the mixed liquid; the mixed solution was poured into a 50 mL polytetrafluoroethylene-lined reactor, and reacted in a blast drying oven at 160°C for 24 hours. After the reaction was completed, the reactor was cooled to room temperature. After the reaction was completed, the precipitate was collected, centrifuged, cleaned, and vacuum dried (50°C, 4h). The obtained sample was passed through H at 900°C. 2 After annealing for 2 h, FeNi nanoparticles were obtained.
[0028] Further, the preparation method of CoFe nanoparticles: 1.0mmol FeCl 2 ·4H 2 O and 20mL of diphenyl ether were added to a four-necked flask, the air in the flask was evacuated with an oil pump, and argon was introduced for 30 minutes; 3.0mmol of triphenylphosphine was weighed and added to the flask, the flask was heated to 100℃, 1.0mmol of oleic acid was added, and the flask was continued to be heated to 260℃; 2.5mL of LiHBEt was weighed using a glass syringe 3 (1.0 mmol tetrahydrofuran) was added dropwise into the flask. When the temperature returned to 260°C, 1.0 mmol Co 2 (CO)8 Add 10 mL of diphenyl ether to completely dissolve it, add it dropwise into the flask, and stir rapidly; after reflux for 30 minutes under the protection of argon, stop heating and cool to room temperature. Add an appropriate amount of ethanol to the obtained solution and centrifuge (8000 rpm, 5 minutes), remove the supernatant, and keep the precipitate. The nanoparticles are redissolved in n-hexane, and the operation is repeated three times to obtain CoFe nanoparticles, which are dried in a vacuum oven (50°C, 4 hours), and the obtained sample is vacuum annealed at 500°C for 40 minutes to obtain CoFe nanoparticles.
[0029] A preparation method based on soft magnetic nanoparticle 3D printing ink is used in the manufacture of chip-level extremely weak magnetic magnetometer magnetic shielding devices.
[0030] A preparation method of soft magnetic nanoparticle 3D printing ink is used in the manufacture of a test panel for a cardio-cerebral magnetic medical device.
[0031] The beneficial effects of this application are:
[0032] First, the first invention point of the present invention is: in order to solve the magnetic shielding requirements of low-frequency magnetic shielding devices in ultra-high sensitivity magnetometers, such as special-shaped parts such as helmets and magnetic test panels in cardio-cerebral magnetic devices, and extremely small devices in chip-level magnetometers, a method is provided to use 3D printing technology, using PDSM as a base material for 3D printing materials, and to form soft magnetic nanoparticles (Fe 3 O 4 Nanoparticles, FeNi nanoparticles and CoFe nanoparticles) are used as fillers for 3D printing materials. Combined with the magnetic shielding properties of soft magnetic materials, the 3D printed devices have magnetic shielding effects, meeting the needs of portability and miniaturization, and are used in medical devices such as helmets and heart magnetic test panels for brain magnetic testing devices, as well as chip-level extremely weak magnetic magnetometer magnetic shielding devices.
[0033] Second, the present invention combines soft magnetic nanoparticles with a 3D printing matrix, so that the printed device has a magnetic shielding effect. The present invention uses different proportions of soft magnetic nanoparticles mixed into the matrix material to obtain the optimal soft magnetic nanoparticle ratio range: 20% to 40%.
[0034] The lower limit of the proportion of soft magnetic nanoparticles is controlled by the relative magnetic permeability. When the proportion of soft magnetic nanoparticles is greater than 20%, the relative magnetic permeability is greater than 1.0; and the upper limit of soft magnetic nanoparticles is determined by the rheological properties of the printing ink. When the proportion of soft magnetic nanoparticles is greater than 40%, it is not easy to flow.
[0035] Third, the second invention of this application is to propose an application. For the helmets and cardio-cerebral magnetic medical devices used in medicine, the shapes are irregular, and the soft magnetic alloys cannot be made into suitable shapes. This application applies soft magnetic nanoparticles to 3D printing technology. Through 3D printing, the design can be simply completed through modeling design. At the same time, the problem of the small size of the magnetometer at the chip pole can also be solved through 3D printing. That is, the technical solution proposed in this application is applied to cardio-cerebral magnetic medical devices with special shapes and chip-level extremely weak magnetic magnetometer shielding devices, which has specific and clear application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The present invention will be further described in detail below in conjunction with the embodiments in the accompanying drawings, but this does not constitute any limitation to the present invention.
[0037] Figure 1 This is a flow chart of the preparation of the soft magnetic nanoparticle-based 3D printing ink and its application in the field of magnetic shielding.
[0038] Figure 2 This is the structural diagram of the magnetic field test board.
[0039] Figure 3 This is the structural diagram of the brain magnetic helmet. DETAILED DESCRIPTION
[0040] <Technical Requirements>
[0041] The technical requirement of this application is to prepare direct-write 3D printing ink, and use the prepared 3D printing ink to print helmets and cardio-cerebral magnetic medical devices in extremely weak magnetic magnetometer shielding devices, as well as some magnetic shielding devices in chip-level extremely weak magnetometers.
[0042] <Technical issues and R&D ideas>
[0043] (1) Can adding soft magnetic nanoparticles to the base of 3D printed materials produce better magnetic shielding materials for use in magnetic shielding devices?
[0044] For this problem, it is necessary to analyze the principle of magnetic flow shunt of low-frequency and static magnetic fields. To shield low-frequency and static magnetic fields, high magnetic permeability soft magnetic materials are needed for shielding. Different high magnetic permeability soft magnetic nanoparticles (Fe 3 O 4 Nanoparticles, FeNi nanoparticles and CoFe nanoparticles) have a good magnetic shielding effect under low frequency and static magnetic field, and the higher the content of soft magnetic nanoparticles with high magnetic permeability, the better the magnetic shielding effect.
[0045] (2) How to determine the ratio of soft magnetic nanoparticles to PDSM?
[0046] To solve this problem, by adjusting the soft magnetic nanoparticles with different high magnetic permeabilities (Fe 3 O 4 The proportion of FeNi nanoparticles and CoFe nanoparticles mixed into the matrix material can achieve a good magnetic shielding effect. However, during the 3D material printing process, the rheological properties of the mixed 3D printing ink determine the feasibility of this 3D printing process.
[0047] <Basic technical solutions>
[0048] The basic technical solution of this application:
[0049] (1) Fe is used in this application 3 O 4 Nanoparticles, FeNi nanoparticles, CoFe nanoparticles and other three kinds of soft magnetic nanoparticles, the above three kinds of soft magnetic nanoparticles have good magnetic shielding effect under low frequency and static magnetic field (among which, the magnetic permeability of FeNi nanoparticles and CoFe nanoparticles will be better after annealing). In particular, it was found in the experiment that the higher the content of soft magnetic nanoparticles with high magnetic permeability, the better the magnetic shielding effect.
[0050] (2) By adjusting the soft magnetic nanoparticles with different high magnetic permeabilities (the soft magnetic nanoparticles are selected from Fe 3 O 4 The optimal content of soft magnetic nanoparticles is determined by mixing the proportion of any one or more of soft magnetic nanoparticles, FeNi nanoparticles, and CoFe nanoparticles into the matrix material and testing the magnetic shielding effect.
[0051] The test method is as follows:
[0052] Take 2.0g of PDSM and place it in a 10mL sample bottle. Take an appropriate amount of soft magnetic nanoparticles (for the convenience of explanation, Table 1 is based on Fe 3 O 4 Take the example for illustration) and configure it to a mass ratio of 0-50% (5%, 10%, 20%, 30%, 40% and 50%), add an appropriate mixture of n-hexane and stir it evenly with a mixer, place it in a vacuum drying oven to dry and remove the mixture to obtain a soft magnetic material ink for direct writing 3D printing. Transfer the material to a 5.0mL barrel, degas it by centrifuge, and then vacuum it in a vacuum drying oven at room temperature to remove bubbles and organic matter. Repeat this operation 3-5 times until the vacuum does not produce bubbles, which can be considered to be removed. Select a needle of appropriate size and install it on the barrel, and then you can do the corresponding printing work.
[0053] Table 1 Rheological and magnetic properties tests of 3D printing inks
[0054] <![CDATA[Printing inks containing Fe with different mass percentages 3 O 4 > Saturation magnetization Relative magnetic permeability <![CDATA[Fe 3 O 4 Nanoparticles]]> 62.0emu / g 1.92 <![CDATA[5%Fe 3 O 4 -PDSM]]> 2.7emu / g 0.84 <![CDATA[10%Fe 3 O 4 -PDSM]]> 5.9emu / g 0.91 <![CDATA[20%Fe 3 O 4 -PDSM]]> 11.5emu / g 1.04 <![CDATA[30%Fe 3 O 4 -PDSM]]> 17.7emu / g 1.16 <![CDATA[40%Fe 3 O 4 -PDSM]]> 23.2emu / g 1.26 <![CDATA[50%Fe 3 O 4 -PDSM]]> 30.3emu / g 1.41
[0055] It can be seen from the above test results that as the mass percentage of soft magnetic material increases, the saturation magnetization intensity and relative magnetic permeability of the printing ink will increase.
[0056] However, correspondingly, as the mass percentage of the soft magnetic material particles increases, the fluidity of the printing ink will deteriorate, so the mass percentage of the soft magnetic nanoparticles is controlled within the range of 20 to 40%.
[0057] <Example 1: Preparation method of 3D printing ink based on soft magnetic nanoparticles>
[0058] Figure 1 A method for preparing a 3D printing ink based on soft magnetic nanoparticles comprises the following steps:
[0059] S1, prepare Fe 3 O 4 Nanoparticles, FeNi nanoparticles, CoFe nanoparticles.
[0060] S1-1, Preparation of Fe by hydrothermal synthesis 3 O 4 Nanoparticles.
[0061] Weigh 0.706g Fe(acac) 3 (2mmol) was added to a beaker, followed by addition of 2.4mL oleic acid and 38mL ethanol to the beaker, and stirred vigorously for 10 minutes using a magnetic stirrer. The evenly mixed solution was poured into a 50mL polytetrafluoroethylene-lined reactor, and reacted in a forced air drying oven at 180°C for 12 hours. After the reaction was completed, the reactor was cooled to room temperature. After the reaction was completed, the precipitate was collected in n-hexane. Add excess ethanol and centrifuge (8000rpm, 5min), remove the supernatant, and retain the precipitate. The nanoparticles were redissolved in n-hexane, the operation was repeated three times, and dried in a vacuum drying oven (50°C, 4h) to obtain the oil phase of Fe 3 O 4 Nanoparticles.
[0062] S1-2, FeNi nanoparticles were prepared by hydrothermal synthesis.
[0063] According to the molar ratio of 60:40, 1.21 g of Fe(NO 3 ) 3 9H 2 O (3 mmol) and 0.58 g Ni(NO 3 ) 2 6H 2O (2mmol) was added to 30mL of deionized water, and then 30mL of N-methylpyrrolidone was added thereto. The mixture was stirred for 10min using a magnetic stirrer and ultrasonicated until the material was evenly dispersed in the mixed liquid. The mixed solution was poured into a polytetrafluoroethylene-lined reactor and reacted in a blast drying oven at 160°C for 24h. After the reaction was completed, the reactor was cooled to room temperature. After the reaction was completed, the precipitate was collected, centrifuged, washed and vacuum dried. The obtained sample was passed through H at 900°C. 2 After annealing for 2 h, FeNi nanoparticles were obtained.
[0064] S1-3, preparation of CoFe nanoparticles by high temperature pyrolysis method.
[0065] 1.0 mmol FeCl 2 ·4H 2 O and 20 mL of diphenyl ether were added to a four-necked flask. The air in the flask was evacuated with an oil pump, and argon was introduced for 30 min. 3.0 mmol of triphenylphosphine was weighed and added to the flask. The flask was heated to 100 °C, 1.0 mmol of oleic acid was added, and the flask was heated to 260 °C. 2.5 mL of LiHBEt was weighed using a glass syringe. 3 (1M tetrahydrofuran) was added dropwise into the flask. When the temperature returned to 260°C, 1.0 mmol of Co 2 (CO) 8 Add 10 mL of diphenyl ether to completely dissolve it, add it dropwise into the flask and stir rapidly. After reflux for 30 minutes under the protection of argon, stop heating and cool to room temperature. Add an appropriate amount of ethanol to the obtained solution and centrifuge (8000 rpm, 5 minutes), remove the supernatant and keep the precipitate. The nanoparticles are redissolved in n-hexane, and the operation is repeated three times. The obtained sample is vacuum annealed at 500°C for 40 minutes to obtain CoFe nanoparticles.
[0066] S2, combining the soft magnetic nanoparticles with the 3D printing matrix to prepare 3D printing soft magnetic ink (adding the soft magnetic nanoparticles to the PDSM, mixing evenly and removing the bubbles, as the soft magnetic material ink for direct writing 3D printing):
[0067] Take 2.0g of PDSM and place it in a 10mL sample bottle, take an appropriate amount of soft magnetic nanoparticles to make a mass ratio of 0-50% (5%, 10%, 20%, 30%, 40% and 50%), add an appropriate mixture of n-hexane and stir evenly with a mixer, place it in a vacuum drying oven to dry and remove the mixture to obtain a soft magnetic material ink for direct writing 3D printing. Transfer the material to a 5.0mL barrel, degas it by centrifuge, and then vacuum it in a vacuum drying oven at room temperature to remove bubbles and organic matter. Repeat this operation 3-5 times until the vacuum no longer produces bubbles, which can be considered to be removed. Select a needle of a suitable size and install it on the barrel, and then you can do the corresponding printing work.
[0068] <Example 2: Application of the preparation method of 3D printing ink based on soft magnetic nanoparticles>
[0069] The 3D printing ink obtained in Example 1 was used to 3D print magnetic shielding devices. A three-axis direct-write printer was used for printing, and Solidwork and other drawing software were used to give the shape and size of the medical device's central brain magnetic test device helmet, heart magnetic test panel, and chip-level extremely weak magnetic magnetometer shielding device, which can be customized for different groups of people. 3 O 4 Nanoparticles, FeNi nanoparticles and CoFe nanoparticles), by mixing 3D printing ink with a suitable mass ratio of soft magnetic nanoparticles, printing with a three-axis direct writing printer, placing it in a drying oven for heating to shape the printed ligand embryo, and obtaining a magnetic shielding device used in the magnetic shielding device.
[0070] The above embodiments are preferred implementation modes of the present invention and are only used to facilitate the explanation of the present invention. They are not intended to limit the present invention in any form. Any person with ordinary knowledge in the relevant technical field, if they do not depart from the scope of the technical features of the present invention, can make equivalent embodiments by partial changes or modifications made by the technical contents disclosed in the present invention, and they do not depart from the technical features of the present invention. They are still within the scope of the technical features of the present invention.
Claims
1. A method for preparing 3D printing ink based on soft magnetic nanoparticles, characterized in that: The following steps are involved: S100, preparing soft magnetic nanoparticles; the soft magnetic nanoparticles are any one or more of Fe3O4 nanoparticles, FeNi nanoparticles, and CoFe nanoparticles; the particle size of the soft magnetic nanoparticles is 5 to 30 nm; S200, adding soft magnetic nanoparticles into PDSM, mixing evenly and removing bubbles to prepare soft magnetic material ink for direct writing 3D printing; the mass of the soft magnetic nanoparticles accounts for 20% to 40% of the sum of the mass of the soft magnetic nanoparticles and the PDSM.
2. A method for preparing a 3D printing ink based on soft magnetic nanoparticles according to claim 1, characterized in that: Step S200 includes the following sub-steps: S201, taking 1 g of PDSM and placing it in a 10 mL sample bottle, and then taking a certain amount of soft magnetic nanoparticles, stirring them evenly with a stirrer to obtain a soft magnetic material ink for direct writing 3D printing; S202, transferring the material into a 5.0 mL barrel, degassing it through a centrifuge, and then vacuuming it in a vacuum drying oven at room temperature to remove bubbles and organic matter, and repeating this operation 3 to 5 times until no bubbles are generated during vacuuming.
3. The method for preparing a 3D printing ink based on soft magnetic nanoparticles according to claim 1, characterized in that: Fe3O4 nanoparticles were prepared by hydrothermal synthesis: 2 mmol of Fe(acac)3 was weighed and added to a beaker, 38 mL of alcohol and 2.4 mL of oleic acid were added, and the solution was stirred for 10 min to mix the solution evenly. The mixed liquid was added to a 50 mL reactor and reacted at 180 °C in a forced air drying oven for 12 h; the mixture was washed with alcohol and n-hexane alternately for 3 times, and the product was placed in a vacuum drying oven to dry.
4. The method for preparing a 3D printing ink based on soft magnetic nanoparticles according to claim 1, characterized in that: Preparation method of FeNi nanoparticles: First, 1.5 mmol of Fe(NO3)3·9H2O and 1.0 mmol of Ni(NO3)2·6H2O were weighed and added into 15 mL of deionized water in a molar ratio of 60:40; Secondly, 15 mL of N-methylpyrrolidone was added thereto, stirred with a magnetic stirrer for 10 minutes, and ultrasonicated until the material was evenly dispersed in the mixed liquid; Again, the mixed solution was poured into a 50 mL polytetrafluoroethylene-lined reactor, and reacted in a blast drying oven at 160° C. for 24 h. After the reaction was completed, the reactor was cooled to room temperature; Finally, after the reaction is completed, the precipitate is collected, centrifuged, cleaned and vacuum dried; the obtained sample is annealed at 900°C for 2 hours under H2 to obtain FeNi nanoparticles.
5. The method for preparing a 3D printing ink based on soft magnetic nanoparticles according to claim 1, characterized in that: Preparation method of CoFe nanoparticles: First, 1.0mmol FeCl2·4H2O and 20mL diphenyl ether were added to a four-necked flask, the air in the flask was evacuated with an oil pump, and argon was introduced for 30 minutes; 3.0mmol triphenylphosphine was weighed and added to the flask, the flask was heated to 100℃, 1.0mmol oleic acid was added, and the flask was continued to be heated to 260℃; Secondly, use a glass syringe to weigh 2.5 mL of LiHBEt3 and add it dropwise into the flask. When the temperature rises to 260°C, weigh 1.0 mmol of Co2(CO)8 and add 10 mL of diphenyl ether to completely dissolve it. Add it dropwise into the flask and stir rapidly. Again, reflux for 30 min under the protection of argon, stop heating and cool to room temperature. Add an appropriate amount of ethanol to the resulting solution and centrifuge, remove the supernatant and keep the precipitate; Finally, the nanoparticles were redissolved in n-hexane, and the operation was repeated three times. The sample was then dried in a vacuum oven, and the obtained sample was vacuum annealed at 500° C. for 40 min to obtain CoFe nanoparticles.
6. Application of the preparation method of soft magnetic nanoparticle 3D printing ink as described in any one of claims 1 to 5 in the manufacture of chip-level extremely weak magnetic magnetometer magnetic shielding devices.
7. Application of the preparation method of soft magnetic nanoparticle 3D printing ink as described in any one of claims 1 to 5 in the preparation of a test panel for a cardio-cerebral magnetic medical device.